Standard b-value DWI-derived stiffness index analysis may provide a way to evaluate the development of intracerebral hematoma - Li, Qian; Mao, Jin; Wang, Qiyuan; Yao, Liding; Xu, Fangfang; Dong, Fei (Frontiers in Neurology, 2025)
Background and purposeThe development of intracerebral hemorrhage (ICH) is closely related to mechanical forces. However, noninvasively evaluating mechanical forces for ICH patients in the current clinical setting is challenging. In this study, we aimed to build an easily accessible stiffness index (STI) and evaluate the stiffness of the perihematomal edema (PHE) region in ICH patients.Materials and methodsIn this retrospective study, two cohorts of 57 patients were included. One cohort (the exploratory cohort) comprised patients with both standard b-value diffusion-weighted imaging (sDWI) (b-values of 0 and 1,000 s/mm2, b0 and b1000) and higher b-value diffusion-weighted imaging (hDWI) (b-values of 200 and 1,500 s/mm2). Another cohort (the hemorrhage cohort) consisted of patients who were diagnosed with ICH and who underwent sDWI within 48 h from onset. The hDWI-based virtual shear modulus (μdiff) was calculated and correlated with the sDWI data in the exploratory cohort. In the hemorrhage cohort, STI maps that were used to estimate μdiff were generated. The mean STI (mSTI) and coefficient of variation (COV) of the STI were computed on the basis of the STI maps in the whole and largest-slice PHE regions.ResultsThe STI could be calculated with the Equation 0.047697*S1000-0.022944*S0 + 5.359883, where S1000 and S0 represent the signal intensities of the b1000 and b0 images, respectively. In the whole and largest-slice PHE regions, both the mSTI and COV were correlated with the hematoma volume (p < 0.01), but neither were correlated with the time from onset.ConclusionThe standard b-value DWI-derived stiffness index analysis may provide a noninvasive and easily accessible way to evaluate the development of ICH.